2004
DOI: 10.1111/j.1439-0329.2004.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Eucalyptus globulus wound wood extractives: evidence of superoxide dismutase‐like activity

Abstract: Superoxide dismutase-like activity of crude Eucalyptus globulus extracts obtained from new wound wood was measured using the water-soluble tetrazolium salt (WST)-1 assay. This in vitro assay determined the activity of superoxide radicals scavenging in a xanthine oxidase system. The 50% inhibition (IC 50 ) of formazan formation was estimated for fractionated samples and purified compounds isolated from the crude wound wood extract, i.e. engelitin and pedunculagin. Standards of gallic acid and pentagalloyl gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…The attenuation of renal damage was confirmed by microscopic examination. These findings are in agreement with those reported in an earlier study [34]. Previous studies indicate that nutraceutical benefits of the extract of our plant have been attributed to the flavonoids and phenolic compounds it contains [35].…”
Section: Discussionsupporting
confidence: 96%
“…The attenuation of renal damage was confirmed by microscopic examination. These findings are in agreement with those reported in an earlier study [34]. Previous studies indicate that nutraceutical benefits of the extract of our plant have been attributed to the flavonoids and phenolic compounds it contains [35].…”
Section: Discussionsupporting
confidence: 96%
“…This activity is probably due to the presence of hydrolysable tannins in both organs with their predominance in fruits. Our results are in agreement with those reported by Eyles et al (2004), these authors have estimated the superoxide dismutase-like activity of crude E. globulus extracts obtained from wounded wood using the water-soluble tetrazolium salt assay, they concluded that the fraction which contains hydrolysable tannins including pedunculagin, di-, tri-and tetragalloylglucose as well as the standard compounds pentagalloyl glucose and pedunculagin showed the highest levels of antioxidant activity. In addition, it has been reported that the antioxidant activity of gallotannins increased with increasing number of galloyl groups (Tian et al, 2009).…”
Section: Figuresupporting
confidence: 83%
“…Thus, healthy trees were strongly associated with polysaccharidases which can break down carbohydrates and release glucose as a source of available energy. Rubber trees can respond to such wounds or stresses by producing defensive chemicals including polyphenol as tannins (Eyles et al 2004). This effect may result from the difference in chemical composition between the leaves from healthy and affected trees which could have an impact on the quality of the litter and consequently on enzyme activities.…”
Section: Discussionmentioning
confidence: 99%